Addressing Corruption Openly. (International Monetary Fund, 2016)
This paper outlines the IMF's perspective on the economic impact of corrup-tion and experience in helping countries design and implement strategies to address it. Corruption has a broader corrosive impact on society. It undermines trust in government and erodes the ethical standards of private citizens. A holistic, multi-faceted approach is needed-one that establishes appropriate incentives and the rule of law, promotes transparency, and introduces economic reforms that reduce opportunities for illicit behavior. Perhaps the most important ingredient for a successful anticorruption approach is the development of strong institutions, centered on a professional civil service that is sufficiently independent from both private influence and political interference. Corruption afflicts countries at all stages of development. Indeed, some developing countries score better on corruption indices than many advanced countries. Corruption has a pernicious effect on the economy. Pervasive corruption makes it harder to conduct sound fiscal policy. Corruption also undermines certain types of public expenditure to the detriment of economic performance.